Comparative Genomics of Pseudomonas stutzeri Complex: Taxonomic Assignments and Genetic Diversity - Li, Xiangyang; Yang, Zilin; Wang, Zhao; Li, Weipeng; Zhang, Guohui; Yan, Hongguang (Frontiers in Microbiology, 2022)
Pseudomonas stutzeri is a species complex with extremely broad phenotypic and genotypic diversity. However, very little is known about its diversity, taxonomy and phylogeny at the genomic scale. To address these issues, we systematically and comprehensively defined the taxonomy and nomenclature for this species complex and explored its genetic diversity using hundreds of sequenced genomes. By combining average nucleotide identity (ANI) evaluation and phylogenetic inference approaches, we identified 123 P. stutzeri complex genomes covering at least six well-defined species among all sequenced Pseudomonas genomes; of these, 25 genomes represented novel members of this species complex. ANI values of ≥ ~95% and digital DNA-DNA hybridization (dDDH) values of ≥ ~60% in combination with phylogenomic analysis consistently and robustly supported the division of these strains into 27 genomovars (most likely species to some extent), comprising 16 known and 11 unknown genomovars. We revealed that 12 strains had mistaken taxonomic assignments, while 16 strains without species names can be assigned to the species level within the species complex. We observed an open pan-genome of the P. stutzeri complex comprising 13,261 gene families, among which approximately 45% gene families do not match any sequence present in the COG database, and a large proportion of accessory genes. The genome contents experienced extensive genetic gain and loss events, which may be one of the major mechanisms driving diversification within this species complex. Surprisingly, we found that the ectoine biosynthesis gene cluster (ect) was present in all genomes of P. stutzeri species complex strains but distributed at very low frequency (43 out of 9548) in other Pseudomonas genomes, suggesting a possible origin of the ancestors of P. stutzeri species complex in high-osmolarity environments. Collectively, our study highlights the potential of using whole-genome sequences to re-evaluate the current definition of the P. stutzeri complex, shedding new light on its genomic diversity and evolutionary history.